2010
DOI: 10.1177/104063871002200426
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis and Osteomyelitis Associated with Enterococcus Cecorum Infection in Broiler and Broiler Breeder Chickens in Ontario, Canada

Abstract: Abstract. In August 2008, an Ontario broiler chicken flock experienced an outbreak of lameness in 4-week-old birds, with morbidity reaching 7% by day 3. Necropsy examination and histopathology revealed arthritis of the hock, stifle, and coxofemoral joints, and femoral and vertebral osteomyelitis. Enterococcus cecorum was isolated from the lesions and identified by 16S ribosomal RNA sequencing. In October 2008, a second case of E. cecorum osteomyelitis involved a flock of 9-week-old broiler breeder chickens, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 6 publications
7
101
2
3
Order By: Relevance
“…In our research, vertebral osteomyelitis was etiologically related to E. coli infection and the simultaneous occurrence of FHN, arthritis, and osteomyelitis in these flocks. The observed macroscopic lesions did not differ by location from the case of spondylitis associated with Enterococcus cecorum (Stalker et al, 2010;Martin et al, 2011), yet differed from the report of spondylitis associated with Aspergillus fumigatus, in which case cervical vertebrae were also affected apart the thoracic vertebrae (van Veen et al, 1999).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In our research, vertebral osteomyelitis was etiologically related to E. coli infection and the simultaneous occurrence of FHN, arthritis, and osteomyelitis in these flocks. The observed macroscopic lesions did not differ by location from the case of spondylitis associated with Enterococcus cecorum (Stalker et al, 2010;Martin et al, 2011), yet differed from the report of spondylitis associated with Aspergillus fumigatus, in which case cervical vertebrae were also affected apart the thoracic vertebrae (van Veen et al, 1999).…”
Section: Discussioncontrasting
confidence: 43%
“…The data from these studies showed occurrences of scoliosis, angular deformity of the spinal canal and joint osteochondrosis in approximately 60% of the birds. Cases of spondylitis in broiler chickens were described in association with infectious agents such as Staphylococcus aureus (Carnaghan, 1966), Enterococcus cecorum (Aziz and Barnes, 2007;Stalker et al, 2010), Aspergillus fumigatus (van Veen et al, 1999). Spondylosis of enzootic origin was described in turkeys (Friedman et al, 1988), as well as a single case of cervical spondylosis in a black swan (Hultgren et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Common enterococcal infections include those of the urinary tract, bloodstream, endocardium and wounds (Shepard & Gilmore, 2002). Although relatively rare, infections by Enterococcus faecalis (Chadfield et al, 2004), Enterococcus hirae (Chadfield et al, 2005), Enterococcus durans (Abe et al, 2006) and Enterococcus cecorum (Stalker et al, 2010) have been described in poultry, and in other birds such as canaries and psittacines (Devriese et al, 1990(Devriese et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant enterococci have been increasingly identified as the most important pathogens responsible for nosocomial infections in man (Top et al, 2007). Common enterococcal infections include those of the urinary tract, bloodstream, endocardium and wounds (Shepard & Gilmore, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the maxillofacial area, the jawbone is the major affected bone (Zemann et al, 2011). Recently, Enterococcus cecorum has been recognized as an emergent avian pathogen, related by spondylitis, femoral head necrosis, and osteomyelitis in broiler and broiler breeder flocks in Scotland (Stalker et al, 2010).…”
Section: Osteomyelitismentioning
confidence: 99%